Studies of Mice with a Balanced Complement of 36 Chromosomes Derived from F(1) Hybrids of T1Wh and T1Ald Translocation Homozygotes - White, Beverly J. (1972)
F(1) hybrids with 38 chromosomes, including single T1Wh and T1Ald translocations, resulted when mice homozygous for the Robertsonian translocations T1Wh and T1Ald were crossed. Meiotic studies of the hybrids showed two trivalents, indicating nonhomology of the T1Wh and T1Ald chromosomes. The hybrids had frequent (25%) unbalanced meiotic metaphase II complements; one trisomic mouse resulted from six F(1) crosses. The F(1) crosses also produced one mouse with 36 chromosomes homozygous for both T1Wh and T1Ald, as well as mice with balanced polymorphic complements of 37, 38, 39, and 40 chromosomes. By crossing the F(2), a homogeneous line with 36 chromosomes was established. The line is phenotypically normal, fertile, and has balanced meiotic metaphase II complements. Analysis of the chromosomes of these mice with quinacrine mustard and the Giemsa-banding technique confirmed that T1Wh and T1Ald consisted of chromosomes 5;19 and 6;15, respectively. Crosses between this line and other existing translocation stocks may produce new strains of mice with even further reduction in chromosome number. Accumulation of Robertsonian translocations, a possible evolutionary mechanism in the wild, can be studied in the laboratory. F(1) hybrids from certain crosses are also an important model for human translocation carriers; both have similar meiotic abnormalities and often have aneuploid offspring.